Peritoneal or mesenteric tumours revealing histiocytosis - Dominique Cazals-hatem; Fleur Cohen-Aubart; Julien Haroche; Abdellatif Tazi; Jean-François Emile; Andreas Seeber; Zofia Hélias-Rodzewicz; Jean Donadieu; Frédéric Charlotte; Janick Selves; Irena Ungureanu; Jerome Razanamahery; et al. (BMJ Open Gastroenterology)
Objective Peritoneal or mesenteric tumours may correspond to several tumour types or tumour-like conditions, some of them being represented by histiocytosis. This rare condition often poses diagnostic difficulties that can lead to important time delay in targeted therapies. Our aim was to describe main features of histiocytoses with mesenteric localisation that can improve the diagnostic process.Design We performed a retrospective study on 22 patients, whose peritoneal/mesenteric biopsies were infiltrated by histiocytes.Results Abdominal pain was the revealing symptom in 10 cases, and 19 patients underwent surgical biopsies. The diagnosis of histiocytosis was proposed by initial pathologists in 41% of patients. The other initial diagnoses were inflammation (n=7), sclerosing mesenteritis (n=4) and liposarcoma (n=1). The CD163/CD68+CD1a- histiocytes infiltrated subserosa and/or deeper adipose tissues in 16 and 14 cases, respectively. A BRAFV600E mutation was detected within the biopsies in 11 cases, and two others were MAP2K1 mutated. The final diagnosis was histiocytosis in 18 patients, 15 of whom had Erdheim-Chester disease. The median diagnostic delay of histiocytosis was 9 months. Patients treated with BRAF or MEK inhibitors showed a partial response or a stable disease. One patient died soon after surgery, and five died by the progression of the disease.Conclusion Diagnosis of masses arising in the mesentery should be carefully explored as one of the possibilities in histiocytosis. This diagnosis is frequently missed on mesenteric biopsies. Molecular biology for detecting the mutations in BRAF or in genes of the MAP kinase pathway is a critical diagnostic tool.